An IL-6 gene in humphead snapper (Lutjanus sanguineus): Identification, expression analysis and its adjuvant effects on Vibrio harveyi OmpW DNA vaccine. Issue 95 (December 2019) - Huang, Pujiang; Cai, Jia; Yu, Dapeng; Tang, Jufen; Lu, Yishan; Wu, Zaohe; Huang, Yucong; Jian, Jichang
Abstract: Interleukin 6 (IL-6) is a pleiotropic cytokine that plays important role in mediating the innate and adaptive immune responses against pathogen infection. In this study, an IL-6 homolog (Ls-IL6) was identified and characterized from humphead snapper, Lutjanus sanguineus . The full-length cDNA of Ls-IL6 was 1066 bp, containing an open reading frame (ORF) of 639 bp encoding 212 amino acids, 5′ untranslated region(UTR) of 63 bp and 3' UTR of 605 bp. The predicted Ls-IL6 protein had typical motif of IL-6 family and shared high identities to teleost IL-6s. Ls-IL6 extensively expressed in various tissues, and the highest expression of Ls-IL6 was detected in head kidney, spleen and thymus. In vivo, the transcript levels of Ls-IL6 were significantly up-regulated in response to Vibrio harveyi infection. Moreover, the DNA plasmid containing the OmpW of V. harveyi together with the gene encoding Ls-IL6 were successfully constructed and administered to fish, the protective efficacy of Ls-IL6 was investigated. Compared with the pcDNA-OmpW group, the level of specific antibodies against V. harveyi increased in pcDNA-IL6-OmpW injected group. After V. harveyi infection, the pcDNA-IL6-OmpW vaccinated fish showed higher relative percent survival (76%) than the relative survival of fish immunized with pcDNA-OmpW (60%). These results indicated that Ls-IL6 was involved in immune response against V. harveyi infection and could be applied as a promising adjuvant for DNA vaccines against V. harveyi . Highlights: Ls-IL6 was cloned and characterized. Ls-IL6 expression was induced by Vibrio harveyi infection in vivo. pcDNA-Ls-IL6-OmpW vaccinated offered higher immune protection compared with pcDNA-OmpW vaccinated in snapper.